My pet and me. - Clark, Olivia (My Pet And Me: Vet Tales, Series 1, 2018)
Rory visits Summer and her pet tortoise Turbo. Together they visit the vet to get Turbo's beak trimmed. Ferne travels to a zoo to meet the vet team who need to check on an amazing armoured animal with a sore foot.